Effects of Long-Term Fertilization and Stand Age on Root Nutrient Acquisition and Leaf Nutrient Resorption of Metasequoia glyptostroboides - Song, Rui; Tong, Ran; Zhang, Hui; Wang, G. Geoff; Wu, Tonggui; Yang, Xiuqing (Frontiers in Plant Science, 2022)
The plant nutrient acquisition strategies are diverse, such as root nutrient acquisition and leaf nutrient resorption, playing important roles in driving soil processes, vegetation performance as well as the ecosystem nutrient cycling. However, it is still in debate that whether above- and below-ground nutrient acquisition strategies co-vary or exhibit coordinated responses to a changing environment, e.g. variation in soil nutrient availability. Herein, this study investigated the responses of root-soil accumulation factor (RSAF) and leaf nutrient resorption efficiency (NuRE) to long-term nitrogen (N) and phosphorus (P) fertilization, and further explored the trade-off between them in Metasequoia glyptostroboides plantations with different stand ages. Results showed that under N fertilization in young plantations, leaf N resorption efficiency (NRE) increased, and root-soil accumulation factor for P (RSAF-P) decreased. For young forests under P fertilization, the NRE increased whereas RSAF-P decreased. For middle-aged forests under P fertilization, the NRE and leaf P resorption efficiency (PRE) increased and t RSAF-P decreased. Under P fertilization in young and middle-aged plantations, PRE was significantly positive correlated with RSAF. Under N fertilization in young plantations, NRE was significantly positive correlated with root-soil accumulation factor for N (RSAF-N). The covariance-based structural equation modeling (CB-SEM) analysis indicted that stand age had positive effects on PRE whether under N or P fertilization, as well as on RSAF-P under N fertilization, whereas had no effects on the NRE or RSAF-N. Overall, our results can shed light on the nutrient acquisition strategies of M. glyptostroboides plantations under future environmental changes and the results could be applied in the nutrient management practices.